Trajectory tracking control for wheeled mobile robots based on nonlinear disturbance observer with extended Kalman filter - Li, Li; Wang, Tianqi; Xia, Yuanqing; Zhou, Ning (Journal of the Franklin Institute, 2020)
This article tackles the trajectory tracking problem for a non-holonomic wheeled mobile robot (WMR) with non-random and random disturbances. A nonlinear disturbance observer with extended Kalman filter (NDEKF) is designed to observe the velocity and the non-random disturbance of the WMR. An error feedback controller and a kinematic controller are proposed to achieve the disturbance compensation and perfect position tracking. The mean square exponential boundedness for the estimation error of NDEKF is presented. Applying the Lyapunov stability theory, it is proved that the velocity and position tracking error of the double closed-loop system are uniformly ultimately asymptotically stable. Finally, numerical simulations demonstrate the validity of the presented methodology.